2016
DOI: 10.1111/pbi.12538
|View full text |Cite
|
Sign up to set email alerts
|

High‐density molecular characterization and association mapping in Ethiopian durum wheat landraces reveals high diversity and potential for wheat breeding

Abstract: SummaryDurum wheat (Triticum turgidum subsp. durum) is a key crop worldwide, and yet, its improvement and adaptation to emerging environmental threats is made difficult by the limited amount of allelic variation included in its elite pool. New allelic diversity may provide novel loci to international crop breeding through quantitative trait loci (QTL) mapping in unexplored material. Here, we report the extensive molecular and phenotypic characterization of hundreds of Ethiopian durum wheat landraces and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
170
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(192 citation statements)
references
References 92 publications
18
170
1
Order By: Relevance
“…The marker-trait associations (MTA) identified for DB and DF in either or both locations combined (Mengistu et al, 2016) were jointly identified by earliness FT (Figure 1B; Table S3). An MTA on chromosome (Chr) 1B was identified by earliness FT and related MTs in both locations.…”
Section: Resultsmentioning
confidence: 95%
“…The marker-trait associations (MTA) identified for DB and DF in either or both locations combined (Mengistu et al, 2016) were jointly identified by earliness FT (Figure 1B; Table S3). An MTA on chromosome (Chr) 1B was identified by earliness FT and related MTs in both locations.…”
Section: Resultsmentioning
confidence: 95%
“…Landraces from this country have unique morphology (Sakamoto and Fukui, 1972; Porceddu et al, 1973; Pecetti et al, 1992) and represent a separate sub-species under the name T. durum subs. abyssinicum or T. aethiopicum (Mengistu et al, 2015, 2016). Figure 4 clearly shows that this germplasm is distinct from the primary region of origin of durum wheat (Middle-East landraces) with substantially no kinship to it.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 85% of durum wheat cultivars grown in Ethiopia in recent decades are landraces (Bechere et al, 1996; Badebo et al, 2009) and over 7,000 accessions have been conserved in the Ethiopian Biodiversity Institute gene bank (Mengistu and Pè, 2016). The investigation of genetic diversity has been initiated in Ethiopian durum wheat landraces at both morphological and molecular levels (Alamerew et al, 2004; Mengistu et al, 2016), and confirmed the uniqueness of Ethiopian wheat to various degrees (Alamerew et al, 2004; Gashaw et al, 2007; Hailu et al, 2010; Mengistu et al, 2016). Although, Porceddu et al (1975) reported Ethiopian landraces were unique sources for rust resistance in early years, no recent studies have characterized the genetic architecture of rust resistance using the genome-wide high-density genetic markers.…”
Section: Introductionmentioning
confidence: 88%